2022
DOI: 10.47892/rgp.2022.421.1337
|View full text |Cite
|
Sign up to set email alerts
|

Open versus minimally invasive sphincter-sparing surgery for rectal cancer: a single-center retrospective cohort study in Peru

Abstract: Objective: The study aimed to describe and compare minimally invasive surgery (MIS) and open surgery for rectal cancer in Peru. Material and methods: A retrospective single-center analysis was performed for all patients who underwent sphincter- sparing surgery for non-metastatic rectal cancer at Instituto Nacional de Enfermedades Neoplásicas in Peru between January 2016 and December 2020. Clinical, perioperative, pathological, and survival outcomes were compared between both groups. A propensity score matching… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…To date the current trend is to perform minimally invasive surgery for colorectal cancer patients, however, this is not the case in developing countries like Peru where most of the cases are still performed with an open approach [ 8 , 10 ]. A meta-analysis by Song et al [ 45 ] concluded that laparoscopic surgery is superior to open in terms of estimated blood loss, hospital stay, postoperative mortality and complications.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To date the current trend is to perform minimally invasive surgery for colorectal cancer patients, however, this is not the case in developing countries like Peru where most of the cases are still performed with an open approach [ 8 , 10 ]. A meta-analysis by Song et al [ 45 ] concluded that laparoscopic surgery is superior to open in terms of estimated blood loss, hospital stay, postoperative mortality and complications.…”
Section: Discussionmentioning
confidence: 99%
“…To date, there is scarce literature regarding this complication and its risk factors in a developing country and Latin population where a high percentage of the surgeries are open instead of laparoscopic, and most of the hospitals do not have enhanced recovery after surgery (ERAS) protocols. For instance, open surgery was the standard of care in the public health system at the beginning of the last decade; despite, there is trend to adopt the laparoscopic approach, there is still around 50%–80% of the cases open during the last 5 years [ 7 10 ]. Hence, our purpose is to identify the pre-, intra- and post-operative risk factors associated with AL from three national hospitals in the capital of Peru to allow the surgeons to make decisions on a daily basis and provide individualised surgical treatment to patients with colorectal cancer.…”
Section: Introductionmentioning
confidence: 99%
“…To avoid interference with these conditions, we used the LNR to assess patient prognosis. The LNR has an important predictive role in patient prognosis and has been validated in colon, esophageal, gastric, bladder, and breast cancers [11][12][13][14][15]. However, in NSCLC, the role of LNR has not been proven.…”
Section: Discussionmentioning
confidence: 99%
“…The LNR has an important predictive role in patient prognosis and has been validated in colon, breast, gastric, esophageal and bladder cancers. This study aims to explore whether the LNR is helpful for predicting the prognosis of patients with stage II NSCLC and whether it can play an important role in the treatment plan [11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%